Parental knowledge, attitudes, and practices toward vaccinating their children against influenza: a cross-sectional study from China - He, Shufeng; Zhu, Caijin; Liu, Xiaoyan; Wang, Yanling (Frontiers in Public Health, 2024)
Aims: Influenza infection is a health burden in children, and the influenza vaccine is an important prevention strategy for flu illness. Parents play a crucial role in children's influenza vaccination. The study aimed to assess parental knowledge, attitudes, and practices (KAP) related to influenza illness for their children, and to explore factors that may impact their decisions.Methods: This cross-sectional study was conducted in a tertiary hospital in Guangzhou from November 2022 to April 2023. Answers to KAP questions regarding influenza illness and vaccination were summed, with a total KAP score of 20. Univariate and multivariate Logistic regression models and linear regression models were conducted to explore the factors associated with influenza vaccination. The results were presented as odds ratios (ORs), β, and 95% confidence intervals (CIs).Results: Overall, 530 parents respondents, of whom 162 (30.56%) had vaccinated their children during the past year. The mean KAP score (standard deviation) was 13.40 (3.57). Compared to parents who reported non-vaccinated for their children in the past year, the parents who reported an influenza vaccination have higher knowledge scores, attitude scores, practice scores, and total scores. Child body mass index, parental education level (under college), parental work (part-time), and more than 2 family members over 60 years old were negatively correlated with knowledge score. Child health condition and knowledge score were positively correlated with attitudes score.And parental age was negatively associated with attitudes score.Though high awareness about influenza illness and vaccination for parents, the coverage rate of influenza vaccination in children was lower in Guangzhou.Implementing public health policies is necessary to spread knowledge about influenza illness and vaccination and to promote the practice of receiving the influenza vaccine in children. Education campaigns would help change the attitudes of parents toward vaccinating their children against the flu. Model 1 Model 2 Variables β (95% CI) P β (95% CI) P Child sex Male Ref Female -0.03 (-0.21-0.14) 0.715 Child age -0.02 (-0.04-0.01) 0.255 Child BMI -0.